2022
DOI: 10.1186/s12879-022-07432-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a novel self-collection method for blood samples and its acceptability for future home-based PrEP monitoring

Abstract: Background Most non-clinic based HIV pre-exposure prophylaxis (PrEP) programs require fingersticks to self-collect blood specimens for laboratory monitoring, a technique that often results in inadequate blood volume for quantitative syphilis and HIV serological testing. We evaluated the acceptability and feasibility of using the Tasso OnDemand™ device as a self-sampling method for PrEP monitoring tests and compared results from samples obtained using the Tasso device to clinician-collected bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
3
18
0
Order By: Relevance
“…Shifting focus to avenues for improvement, some participants recommended the inclusion of prerecorded instructional videos in addition to written instructions, especially for the finger-stick blood sample, to allay their anxiety (by demonstrating how finger-stick blood self-collection differs from phlebotomy conducted in a clinic) and bolster their self-efficacy (by offering an opportunity to perform self-collection alongside someone in the video). We acknowledge that providing access to prerecorded instructional videos is becoming increasingly common in specimen self-collection research [ 65 - 67 ] and concur with those who emphasize that supplemental instructional resources should be accurate and easy to comprehend (including their availability in multiple languages) and should provide clear guidance on how to handle specimens after self-collection [ 23 , 68 ]. On the basis of participants’ feedback, it might also be beneficial to highlight the importance of triple-site bacterial STI testing and reiterate the types of testing that would and would not be performed on hair samples.…”
Section: Discussionmentioning
confidence: 60%
“…Shifting focus to avenues for improvement, some participants recommended the inclusion of prerecorded instructional videos in addition to written instructions, especially for the finger-stick blood sample, to allay their anxiety (by demonstrating how finger-stick blood self-collection differs from phlebotomy conducted in a clinic) and bolster their self-efficacy (by offering an opportunity to perform self-collection alongside someone in the video). We acknowledge that providing access to prerecorded instructional videos is becoming increasingly common in specimen self-collection research [ 65 - 67 ] and concur with those who emphasize that supplemental instructional resources should be accurate and easy to comprehend (including their availability in multiple languages) and should provide clear guidance on how to handle specimens after self-collection [ 23 , 68 ]. On the basis of participants’ feedback, it might also be beneficial to highlight the importance of triple-site bacterial STI testing and reiterate the types of testing that would and would not be performed on hair samples.…”
Section: Discussionmentioning
confidence: 60%
“…Blood collection with a vacuum system was highly acceptable and feasible for sampling among PrEP-using MSM. They were confident of performing this without supervision at home [29]. Saliva-based sampling was also experienced as acceptable and mostly easy to perform [27, 3034].…”
Section: Resultsmentioning
confidence: 99%
“…Additional processing and testing procedures for HIV, syphilis, RPR and creatinine have been described elsewhere. (30) Outcomes and Analyses Primary outcome measures: Effectiveness will be evaluated with a survival analysis using PrEP nonretention as the event of interest. Observation time begins for all participants at the time of randomization and continues until either loss-to-follow-up or study end at 20 months.…”
Section: Specimen Processing and Laboratory Evaluationsmentioning
confidence: 99%
“…Approximately 40% of PHSKC PrEP users have a history of syphilis, of which 25% are serofast (have a persistently positive RPR despite treatment in the past) and require a quantitative RPR for syphilis screening. (30) Although prior HB-PrEP studies used procedures that allowed PrEP users to collect all specimens (gonorrhea/chlamydia [GC/CT] swabs and blood samples) from home, (23,27) nearly all require fingerstick specimens to perform a less accurate rapid HIV antibody test and collected insufficient blood volume to perform RPR titers, limiting the ability to determine whether titers were stable or signified a newly acquired syphilis infection. We previously conducted a pilot study (30) that showed the acceptability and feasibility of using a novel blood self-collection device (Tasso+™) (31) to obtain samples suitable for HIV antigen/antibody and quantitative RPR testing.…”
Section: Introduction Backgroundmentioning
confidence: 99%
See 1 more Smart Citation